A Study on Conjugate Quadrature Filters. (9th March 2011) - Leng, Jin-Song; Huang, Ting-Zhu; Jing, Yan-Fei; Jiang, Wei
Abstract : It is very important for generating an orthonormal multiwavelet system to construct a conjugate quadrature filter (CQF). In this paper, a general method of constructing a length-J + 1 CQF with multiplicityr and scalea from a length-J CQF is obtained. As a special case, we study generally the construction of a length-J + 1 CQF with multiplicity 2 and scale 2 which can generate a compactly supported symmetric-antisymmetric orthonormal multiwavelet system from a length-J CQF.